Performance and mechanism of mold-pressing alkali-activated material from MSWI fly ash for its heavy metals solidification. (1st May 2021) - Shao, Ningning; Wei, Xuankun; Monasterio, Manuel; Dong, Zhijun; Zhang, Zuotai
Graphical abstract: Highlights: Ultra-low dosage of alkaline activator was achieved by introducing mold-pressing technology. High performance for heavy metals solidification by mold-pressing AAM. High compressive strength can be obtained. Abstract: The safe disposal of municipal solid waste incineration fly ash (MSWIFA) has become the weakest link of the circular economy of MSW due to its hazardous nature. In this study, we focused on the heavy metals solidification of MSWIFA by using alkali-activation technology and introducing a mold-pressing method. The influence of alkaline activator (AA) including alkali concentration and dosage of sodium silicate solution were well designed and studied. MSWIFA before and after alkali-activation, as well as the sample treated by commercial chelating agent (CA), were contrastively studied the performance of heavy metals solidification. The results show that the alkali-activated MSWIFA exhibits superior solidification for heavy metals than the blank control and the CA treated ones. With mold-pressing technology, the alkali-activated MSWIFA shows a core-shell structure, in which a thin layer that is composed of mainly N-A-S-H gel is as the shell and acts as a protective layer to inhibit the leaching of heavy metals. Besides, the introduced mold-pressing technology is beneficial for the improvement of materials strength and the reduction of AA dosage. The optimal AA composition is that the net concentration of NaOH is ∼4 M and sodium silicate dosage is ∼65 wt% in alkaline activator, and the total alkaline activator requirement is only 32 wt% of MSWIFA, yielding 7.9 MPa compressive strength at 10.2 MPa molding pressure. In summary, this work paves a potential new way for safe and recycling use of hazardous MSWIFA, which will be of great significance to environmental sustainability.